INISIASI PENDAMPINGAN DAN IDENTIFIKASI PERMASALAHAN KELOMPOK USAHA TANI HUTAN PROHUTANI TAWANGMANGU KARANGANYAR - Dewanti, Ida Susi; Tjahjanti, Rosalia Dwi Fadma; Wulandari, Asih Marini; Zaki, Ahmad; Hapsari, Nurul Retno (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This community service was conducted by lecturers from the Business Administration Department, Universitas Pembangunan Nasional Veteran Yogyakarta, aimed at identifying and assisting the Forest Farming Business Group ProHutani in Tawangmangu, Karanganyar, Central Java. The team mapped out problems and analyzed the situation of the coffee farming business group, identifying issues such as capital, production capacity, business management, and product marketing. The activities were carried out in several stages, including lectures, discussions, and direct interviews with business actors. The identification results indicated the need for training in coffee cultivation, business management, licensing, and marketing. This community service successfully identified several solutions and follow-up steps for the further development of this business group.